Essays on the economics of climate change and networks - Juha V.A. Itkonen (Bank of Finland, 2015)
Climate change is one of the greatest market failures of our time. This thesis consists of three essays in which we study the economics of climate change using networks as a theoretical framework. In the first essay, we discover flaws in the foundations of a recent strand of literature estimating the carbon Kuznets curve (CKC). The CKC hypothesizes that carbon dioxide emissions initially increase with economic growth but that the relationship is eventually reversed. The recent literature attempts to estimate the CKC by adding energy consumption as a control variable. Due to model misspecifications related to the econometric methodology and database definitions, the results are biased to support the existence of a CKC. Consequently, the literature underestimates the need for climate policies. In the second essay, we study how social networks might help to explain why differences of opinion about climate change persist across segments of the lay public despite the scientific consensus. To do this, we programmed a Facebook application that collected survey data on concerns about climate change and network data on friendships. We found that respondents tend to have friends with similar concerns as their own, the unconcerned respondents have fewer friends, and any two respondents who disagreed about the seriousness of global warming were less than half as likely to be friends. The results indicate that the structure of the social network may hinder changes in opinions, explaining why opinions persist despite the scientific consensus. The results suggest that the communication of climate science could be improved by strategies that aim to overcome these network effects. In the third essay, we study permit markets which are connected by a network of links. A link allows participants of one emissions trading system to use permits of other systems. In a linked network of markets, foreign regulators can influence domestic policy outcomes even without a direct link. We apply graph theory to study these dependencies between markets to determine who exactly can affect domestic emissions and prices. We characterize the equilibrium's dependency structure assuming perfect competition and an exogenous trading network. The results help to avoid unexpected foreign interference with domestic policy outcomes and to secure the effectiveness of climate change policies.
URN:NBN:fi:bof-201504301162
Keywords: 330; climate; networks; economics; carbon Kuznets curve; social ties; EEO model; VAR model; Klimawandel; Umweltökonomik; Netzwerkökonomik; Social Web; Klimaschutz; Emissionshandel; Marktstruktur; Graphentheorie; VAR-Modell